Optimización de procesos markovianos de decisión a través de un modelo de programación lineal: el caso de inversión en activos financieros riesgosos - Bouillon, Adolfo G. (2019)
This paper seeks to determine an optimal course of action for investing in risky assets through a linear programming model, adapted to a particular type of decision, known as the Markovian decision process. We analyze stock statistics of three important firms of three industries of representative trading activity and their correlation with the Lima Stock Exchange General Index, with the purpose of establishing a prediction price model for said assets.Then, we formulate a Markovian decision process and prepare a linear programming model for an optimal solution. We find that linear programming modeling reduces the time and complexity of a Markovian decision process in choosing a course of action that maximizes profits upon risky asset investment.